Metabolic disposition of H3B-8800, an orally available small-molecule splicing modulator, in rats, monkeys, and humans. (1st September 2020) - Rioux, Nathalie; Smith, Sherri; Colombo, Federico; Kim, Amy; Lai, W. George; Nix, Darrell; Siu, Y. Amy; Schindler, Joanne; Smith, Peter G.
Abstract: H3B-8800, a novel orally available modulator of the SF3b complex, which potently and preferentially kills spliceosome-mutant tumor cells, is in clinical development for the treatment of advanced myeloid malignancies. We characterized the pharmacokinetics, metabolism and disposition of H3B-8800 in rats, monkeys and humans. In vitro, H3B-8800 is a substrate of CYP3A4/5, flavin-containing monooxygenases (FMOs) and P-glycoprotein (P-gp), and showed a favorable drug–drug interaction profile as a perpetrator. Following oral dosing of 14 C-H3B-8800 in bile-duct cannulated SD rats, 54.7% of the dosed radioactivity was excreted in the bile, with less found in feces (36.8%). The low amount in urine (3.7%), suggests that renal elimination is a minor pathway of clearance for H3B-8800. In Long-Evans rats, radioactivity derived from 14 C-H3B-8800 was rapidly absorbed, with the highest distribution in the ocular, metabolic/excretory, and gastrointestinal tract tissues. No radioactivity was detected in the central nervous system. Seven metabolites were observed in human plasma following 4 daily doses of 40 mg H3B-8800. H3B-68736 ( N -desmethyl), H3B-77176 ( N -oxide), and unchanged H3B-8800 were the prominent components in human plasma, at 27.3%, 18.1%, and 33.2%, respectively, of the total drug-related material in a pooled AUC0–24h sample. The same 7 metabolites were observed in monkey plasma.